Product Design and Alternative Market Schemes for Solid Waste Treatment and Disposal - Thomas Eichner; Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 1999)
In this paper we reexamine the issue of allocating a natural resource 'material' that is extracted, used for producing a consumption good, recycled, and that may cause environmental damage when it is finally landfilled without prior waste treatment. The 'material' explicity enters the analytisis as a factor of production and is then embodied in the output. That is, the embodied material per unit of output (material content) forms, as a matter of product design, an intrinsic attribute of the consumption good and of the solid waste left over after consumption. Since the technologies of both waste treatment and recycling depend on that material content, an issue of green product design arisis (Consumers are assumed to be indifferent with respect to the material content of the consumption good). Our main focus is on clarifying how three different market schemes affect the allocation of embodied material: (i) Lindahl markets, (ii) indirect markets for material content as suggested by Fullerton and Wu (1998) in a similar context, and (iii) markets for embodied material. While the Lindahl markets serve as a theoretical benchmark only, the central message is that - under some serious restrictions regarding technology and the number of agents - each of the markets schemes (ii) and (iii) has the capacity of allocating the material (content) efficiently, provided that the environmental externality is appropriately relevant. It remains an open question, however, which of the market schemes, if any, is empirically relevant. This is also shown in which way the allocation is distorted when the above mentioned material-related markets fail to be active.
Keywords: H21; Q28; 330